Tensile rotary power transmission model development for airborne wind energy systems. Issue 3 (September 2020) - Tulloch, O; Amiri, A Kazemi; Yue, H; Feuchtwang, J; Read, R
Abstract: Rotary airborne wind energy (AWE) systems are a family of AWE devices that utilise networked kites to form rotors. One such device is the Daisy Kite developed by Windswept and Interesting. The Daisy Kite uses a novel tensile rotary power transmission (TRPT) to transfer power generated at the flying rotor down to the ground. Two dynamic models have been developed and compared; one with simple spring-disc representation, and one with multi-spring representation that can take account of more degrees of freedom. Simulation results show that the angular velocity responses of the two TRPT models are more closely correlated in higher wind speeds when the system shows stiffer torsional behaviour. Another interesting point is the observation of two equilibrium states, when the spring-disc TRPT model is coupled with NREL's AeroDyn. Given the computational efficiency of the simpler model and the high correlation of the results between the two models, the simple model can be used for more demanding simulations.